Does capping social security harm health? A natural experiment in the UK. (8th September 2021) - Reeves, Aaron; Fransham, Mark; Stewart, Kitty; Patrick, Ruth
Abstract: In this paper, we examine the mental health effects of lowering the UK's benefit cap in 2016. This policy limits the total amount a household with no‐one in full‐time employment can receive in social security. We treat the reduction in the cap as a natural policy experiment, comparing those at risk of being capped and those who were not, and examining the risk of experiencing poor mental health both before and after the cap was lowered. Drawing on data from 900, 000 individuals, we find that the prevalence of depression or anxiety among those at risk of being capped increased by 2.6 percentage points (95% confidence interval: 1.33–3.88) compared with those at a low risk of being capped. Capping social security may increase the risk of mental ill health and could have the unintended consequence of pushing out‐of‐work people even further away from the labour market.